Answer:
The constant is to add 1/10 to the previous term, therefore the unknown term is 5/10 or 1/2.
And this is the rule:
aₙ = aₙ₋₁ + 1/10 ⇒ a₁ = 3/10
Explanation:
Let's find the unknown term and the sequence:
1st term = 3/10
2nd term = 2/5 = 4/10
3rd term = x
4th term = 3/5 = 6/10
5th term = 7/10
As we can see the constant is to add 1/10 to the previous term, therefore the unknown term is 5/10 or 1/2.
And this is the rule:
aₙ = aₙ₋₁ + 1/10 ⇒ a₁ = 3/10
a₂ = a₁ + 1/10 ⇒ a₂ = 4/10 = 2/5 (Simplifying)
a₃ = a₂ + 1/10 ⇒ a₃ = 5/10 = 1/2 (Simplifying)
a₄ = a₃ + 1/10 ⇒ a₄ = 6/10 = 3/5 (Simplifying)
a₅ = a₄ + 1/10 ⇒ a₅ = 7/10